Kelayakan kualitas air kolam di lokasi pariwisata Embung Klamalu Kabupaten Sorong Provinsi Papua Barat - Yumame, Rut Yullyn; Rompas, Robert; Pangemanan, Penky N.L (Universitas Sam Ratulangi, 2013)
The purpose of research was to analyze water quality parameters including temperature, brightness, pH, dissolved oxygen, alkalinity, and carbon dioxide in tourism area Embung Klamalu, Sorong Regency, West Papua Province. Measurement of water parameters was done in situ and in laboratory. It was found that on week two measurement, water temperature ranged from 27.2 to 28.9 ˚ C in the morning and 28.2 to 30.2 ˚C in the afternoon; brightness from 6.0 to 0.7 and from 7.0 to 7.8, pH 6.0 to 6.8 and from 7.0 to 7.8, DO from 6.10 to 7.35 mg/L; total alkalinity 100 – 160 mg /L and 100 - 140mg/L, carbon dioxide 50.92 to 85.93 mg/L and 55.90 to 75.92 mg/L. It was concluded that parameters of pond water in tourism area Embung Klamalu were still in suitable for aquaculture activity. Keywords: water quality, pond, Embung Klamalu, Sorong Regency